Distribution of Tissue Plasminogen Activator Insertion/Deletion Polymorphism in Myocardial Infarction and Control Subjects - Steeds, Rick; Adams, Matthew; Smith, Pamela; Channer, Kevin; Samani, Nilesh J. (Thrombosis and Haemostasis, 1998)
An insertion (I)/deletion (D) polymorphism in the tissue plasminogen activator (TPA) gene locus has recently been reported to be associated with the risk of myocardial infarction (MI) with increased risk in II/ID subjects compared with DD subjects. To investigate this further, we analysed 529 acute MI cases and 525 population-based control subjects recruited in two centers (Leicester and Sheffield, UK). We found no difference between cases and controls in TPA I/D allele frequencies (cases I = 0.574, controls I = 0.582, p = 0.74) or genotype distribution (cases II 33%, ID 48%, DD 19%; controls II 34%, ID 49%, DD 17%, p = 0.88). Compared with the DD genotype, the age, sex and centre adjusted odds ratios for MI for II genotype was 0.95 (95% confidence interval, 0.64 – 1.40, p = 0.85) and that for ID genotype was 0.89 (0.62-1.27, p = 0.56). There was no significant effect modification by smoking status, body mass index or cholesterol level. There was no difference in the reported frequency of positive family history of coronary heart disease or mean age at MI in the different genotype groups. We conclude that in our populations the TPA I/D polymorphism is not a major independent risk factor for myocardial infarction.